Strategi Pengembangan Karakter Team dalam Pembentukan Karakter Stakeholder di MTs Tarbiyatul Akhlak Gresik - Muhtashor; Fadly Usman (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2021)
Character building carried out at MTs Tarbiyatul Akhlaq Gresik through a learning process, including praying before and after learning. Character building outside of learning hours is the implementation of additional activities outside the main lesson hours, namely extracurricular activities. Qualitative type by describing and describing the cultivation and process of character development of students in the scope of the school. In this study, the researcher observed, witnessed, and observed directly by going down/plunging into the field (research location) namely MTs Tarbiyatul Akhlaq, Gresik. This research was conducted for 3 consecutive months. Data collection methods in this study were observation, interviews, and documentation. In the research process, Miles and Hubarman data analysis techniques are used, namely data reduction, data display and conclusion drawing and verification. Based on the presentation of the research results and discussion as follows. First, the development of character values at MTs Tarbiyatul Akhlaq, Gresik is carried out through learning process activities, namely the steps of determining the learning objectives contained in the Learning Preparation Plan (RPP), determining character values, determining relevant learning strategies and methods, and planning learning based steps. character. Second, the development of character values at MTs Tarbiyatul Akhlaq, Gresik is done through habituation which becomes the culture of the madrasa through the stages of character values; determination of madrasa cultural activities conceptualized into routine activities, spontaneous (unscheduled) activities, and exemplary teachers and employees.